Correlated patterns in hydrothermal plume distribution and apparent magmatic budget along 2500 km of the Southeast Indian Ridge - Baker, Edward T.; Hemond, Christophe; Briais, Anne; Maia, Marcia; Scheirer, Daniel S.; Walker, Sharon L.; Wang, Tingting; Chen, Yongshun John (Geochemistry, Geophysics, Geosystems, 2014)
Multiple geological processes affect the distribution of hydrothermal venting along a mid-ocean ridge. Deciphering the role of a specific process is often frustrated by simultaneous changes in other influences. Here we take advantage of the almost constant spreading rate (65-71 mm/yr) along 2500 km of the Southeast Indian Ridge (SEIR) between 77 degrees E and 99 degrees E to examine the spatial density of hydrothermal venting relative to regional and segment-scale changes in the apparent magmatic budget. We use 227 vertical profiles of light backscatter and (on 41 profiles) oxidation-reduction potential along 27 first and second-order ridge segments on and adjacent to the Amsterdam-St. Paul (ASP) Plateau to map p(h), the fraction of casts detecting a plume. At the regional scale, venting on the five segments crossing the magma-thickened hot spot plateau is almost entirely suppressed (p(h)=0.02). Conversely, the combined p(h) (0.34) from all other segments follows the global trend of p(h) versus spreading rate. Off the ASP Plateau, multisegment trends in p(h) track trends in the regional axial depth, high where regional depth increases and low where it decreases. At the individual segment scale, a robust correlation between p(h) and cross-axis inflation for first-order segments shows that different magmatic budgets among first-order segments are expressed as different levels of hydrothermal spatial density. This correlation is absent among second-order segments. Eighty-five percent of the plumes occur in eight clusters totaling approximate to 350 km. We hypothesize that these clusters are a minimum estimate of the length of axial melt lenses underlying this section of the SEIR. Geochemistry & Geophysics SCI(E) EI 0 ARTICLE edward.baker@noaa.gov 8 3198-3211 15